Experimental infection of goats by Pasteurella multocida B:2 - Saad, Mohd Zamri; N. M. D., Zaitun; A., Ernie; M. S., Shafarin (Veterinary Association Malaysia, 2005)
An experiment was carried out to determine whether goats can be infected by Pasteurella multocida B:2, the causative agent of haemorrhagic septicaemia of cattle and buffaloes. Thirty-six healthy local goats were divided into four groups consisting of nine goats per group. Goats of groups 1 and 3 were inoculated intranasally with 1ml inoculum containing 109 CFU of live P. multocida B:2. Goats of groups 2 and 4 were not infected, but were exposed to the infected animals by keeping goats of group 2 together with group 1 while group 4 together with group 3. Immediately post-infection, goats in groups 3 and 4 were treated with dexamethasone at the rate of 1mg/kg for three consecutive days. Three goats from each of the four groups were killed on days 7,14 and 21 post-infection. One goat from group 3 died percutely on day 2 post-infection, showing lesions typical ofhaemorrhagic septicaemia. Other two goats from the same group were weak. None of the goats in groups 1, 2 and 4 succumbed to the disease but most exhibited signs of mild respiratory tract infection. Post-mortem examinations revealed that 20 (53 %) goats had mild, acute pneumonia affecting less than 7% of the lung, suggesting that P. multocida B:2 is not a primary pathogen of the respiratory tract. Four (11 %) goats of group 3 had pulmonary oedema and congestion, indicating that dexamethasone enhanced chances of goats being infected by P. multocida B:2. P. multocida was successfully re-isolated from lungs and nasal swabs of goats from all groups, and heart blood of goats from group 3 but not from the lymph nodes and tonsils. The re-isolation of P. multocida B:2 was successfully made for up to 14 days p.i, in groups without dexamethasone but for up to 21 days following dexamethasone treatment. Transmission of P. multocida B:2 to the in-contact goats occurred at a rate of 40%.